HONEY AND PROPOLIS IN PUBLIC HEALTH: EVIDENCE, REGULATION, AND TECHNOLOGY-ENABLED QUALITY ASSURANCE - Daria Danielczyk; Michał Babicz; Kamil Chudzicki; Wiktor Czyżewski; Katarzyna Rosa; Agata Słoma; Anna Szot; Dominik Szydełko; Martyna Szymczyk; Paweł Żurek (International Journal of Innovative Technologies in Social Science, 2026)
Bee-derived products such as honey and propolis are increasingly used as foods, supplements, and components of traditional and complementary medicine. At the same time, public health systems face antibiotic overuse, a rising burden of chronic diseases, and an expanding market of natural products whose quality, safety, and claims are variable. This review synthesizes recent peer-reviewed evidence on honey- and propolis-based products with an emphasis on (i) clinically and socially relevant application areas, (ii) public health determinants of safe use (knowledge, regulation, and information pathways), and (iii) modern technologies that can improve standardization, authentication, and consumer protection. A targeted narrative review was conducted using PubMed, PMC, and Google Scholar, prioritizing recent reviews, clinical and preclinical studies, and analytical quality-control research. The literature suggests the strongest and most mature evidence base for symptom relief in selected pediatric respiratory infections, alongside emerging but heterogeneous findings in chronic disease contexts (e.g., metabolic and kidney-disease populations). Across indications, major translation barriers include variability in botanical origin and composition, inconsistent preparations and dosing, contamination and adulteration risks, and uneven professional guidance. Survey data indicate important knowledge gaps among healthcare professionals and highlight social media as a dominant information source, raising concerns about misinformation-driven use. Advances in chemical analytics (spectroscopy, chromatography-mass spectrometry), DNA-based botanical verification, and non-thermal decontamination approaches can strengthen quality assurance. Integrating these technologies with clearer governance and health-professional education may help translate honey and propolis into responsible, evidence-aligned public health practices.